Online collaborative performance in group-based tasks among learners of higher education - Aini Akmar Mohd Kasim; Norizul Azida Darus; Noor Azli Affendy Lee; Asha Latha Bala Subramaniam; Junaidah Januin (Universitas Syiah Kuala, 2022)
Collaborative skills have been perceived as the most important skills by learners, instructors, and employers alike in comparison to communication and entrepreneurial skills. Despite its significant role in the workplace, many find that working together with others may complicate tasks due to limited background knowledge and problems with social dynamics. There has not been a single assessment created to assess online collaboration as an integrated performance during group-based tasks. The present study, therefore, attempts to examine learners’ online collaborative performance and the dimensions contributing to effective online collaboration at the tertiary level. A mixed-method research design was adopted using surveys and interviews. A number of 508 undergraduates from local universities were given a questionnaire inquiring about their online collaborative behaviour in group work, while 30 of them were interviewed. The findings indicated that the communication tools and technological facilities category were rated the highest in online collaborative performance, whereas sharing responsibilities was rated the highest in team dynamics. There was also a significant correlation between online collaborative performance and team dynamics. Interview responses showed that learners agreed that good communication, clear goals, and team commitment were important elements for successful online collaboration. Despite the potential to enhance students’ online collaborative performance, collaborative learning is demanding for learners and educators alike.